SHARELIFE - One Century of Life Histories in Europe - Axel Börsch-Supan; Martina Brandt; Mathis Schröder (Advances in Life Course Research, 2013)
Welfare state interventions shape our life courses in almost all of their multiply linked domains. In this introduction, we sketch how cross-nationally comparative retrospective data can be fruitfully employed to better understand these links and the long-run effects of the welfare state at the same time. We briefly introduce SHARE, the Survey of Health, Ageing and Retirement in Europe, and SHARELIFE, which collected 30,000 life histories of {SHARE} respondents from 14 European countries, providing a unique data infrastructure for interdisciplinary research on the various influences of contextual structures on the lives of Europeans during the last century until today. The eight studies in this special issue show that the multidisciplinary cross national approach of {SHARELIFE} allows a much more detailed understanding of life histories in Europe than was possible before.
Additional information: NOTICE: This is the author's version of a work that was accepted for publication in “Advances in Life Course Research”. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Advances in Life Course Research 18 (2013), 1, pp. 1-4 and is online available at http://dx.doi.org/10.1016/j.alcr.2012.10.009.
Keywords: 330; Ageing; Cross-national research; Interdisciplinary research; Life course perspective; Life history data; Welfare state; Altersgruppe; Gesundheit; Panel; Vergleich; Europa